Renal artery pseudoaneurysm following holmium laser diverticular neck incision for calyceal diverticular stones: a rare case report - Yu, Botao; Wang, Chunling; Zhou, Ningying; Yin, Min (Frontiers in Surgery, 2026)
BackgroundCalyceal diverticulum (CD) is a rare congenital anomaly that predisposes patients to stone formation due to impaired urinary drainage. Flexible ureteroscopy with holmium laser incision of the diverticular neck followed by holmium laser lithotripsy for the associated calculi, particularly when combined with a suction-assisted ureteral access sheath, is a favored minimally invasive approach for managing calyceal diverticular stones. While generally safe, vascular complications are exceptionally rare and potentially life-threatening.Case presentationWe report a rare case involving a 29-year-old man with an upper pole calyceal diverticular stone, who underwent successful fURSL with laser incision of the diverticular neck and complete stone clearance using a suction-assisted access sheath. Five days postoperatively, the patient presented with gross hematuria and flank pain. Conservative management failed, and angiography identified a pseudoaneurysm in an upper-pole branch of the left renal artery. Transcatheter arterial embolization (TAE) was performed, leading to complete resolution of the pseudoaneurysm and bleeding.ConclusionThis case highlights a rare but serious vascular complication of fURSL in patients with narrow neck calyceal diverticula. Surgeons should be aware of the risks of vascular trauma and consider early angiographic evaluation in the setting of delayed hematuria.